Anti‐synthetase syndrome‐associated pulmonary veno‐occlusive disease. (1st June 2020) - Kay, Dana; Kadri, Ferdous; Fitzpatrick, Garrett; Alnuaimat, Hassan; Reddy, Raju; Ataya, Ali
Abstract : Pulmonary arterial hypertension has been reported with a prevalence of 7.9% in patients with anti‐synthetase syndrome; however, anti‐synthetase syndrome associated with pulmonary veno‐occlusive disease (PVOD) has never before been described in the literature. We present a novel case of anti‐synthetase syndrome‐associated PVOD in a patient who presented with hypoxic respiratory failure associated with right heart failure and was diagnosed with anti‐synthetase syndrome based on his autoimmune serology and pre‐capillary pulmonary hypertension on right heart catheterization. He was initiated on pulmonary arterial hypertension therapy, but with escalating dose of parenteral epoprostenol, experienced acute clinical worsening with chest imaging concerning for PVOD that was confirmed on autopsy. Anti‐synthetase syndrome can be associated with PVOD, and it should be suspected in patients who have evidence of pre‐capillary pulmonary hypertension and who deteriorate with the initiation of pulmonary hypertension‐specific therapy.